Partial Splenic Embolization as a Bridge to Total Knee Replacement for a Patient with Severe Thrombocytopenia due to Cirrhosis and Splenic Sequestration - Netterville, Adrianne; Lands, Ronald (Case Reports in Hematology, 2012)
Medical splenectomy by embolization was originally used to attenuate bleeding from varices in a man with cirrhosis and portal hypertension. Despite the procedure being described over 40 years ago with remarkable improvement in its safety profile and clinical outcomes since, it is still used with variable frequency because of concerns that the risk is high and the results are transient. We present the case of an elderly woman with cirrhosis, portal hypertension, and splenic sequestration who completed partial splenic embolization (PSE) with a durable hematologic response that served as a bridge which allowed her to have orthopedic surgery. A discussion with literature review follows.